2009
DOI: 10.1016/j.ccr.2009.03.027
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Autotaxin and Lysophosphatidic Acid Receptors Increases Mammary Tumorigenesis, Invasion, and Metastases

Abstract: SUMMARY Lysophosphatidic acid (LPA) acts through high affinity G protein-coupled receptors to mediate a plethora of physiological and pathological activities associated with tumorigenesis. LPA receptors and autotaxin (ATX/LysoPLD), the primary enzyme producing LPA, are aberrantly expressed in multiple cancer lineages. However, the role of ATX and LPA receptors in the initiation and progression of breast cancer has not been evaluated. We demonstrate that expression of ATX or each Edg-family LPA receptor in mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
319
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(325 citation statements)
references
References 62 publications
5
319
1
Order By: Relevance
“…Mouse model studies have revealed an important role for the ATX-LPA receptor axis in tumor progression as well as in other pathologies, ranging from inflammation to fibrosis (2,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Accordingly, pharmacological inhibition of ATX is an attractive way to interfere with LPA signaling for therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse model studies have revealed an important role for the ATX-LPA receptor axis in tumor progression as well as in other pathologies, ranging from inflammation to fibrosis (2,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Accordingly, pharmacological inhibition of ATX is an attractive way to interfere with LPA signaling for therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Forced overexpression of ATX or individual LPA receptors promotes tumor progression in mouse models (13)(14)(15)(16), while LPA receptor deficiency protects from colon carcinogenesis (17). In addition to its role in cancer, ATX-LPA signaling has been implicated in lymphocyte homing and (chronic) inflammation (18), fibrotic diseases (19 and 20), and thrombosis (21).…”
mentioning
confidence: 99%
“…Furthermore, LPA induced migration in breast cancer cells by activating LPA1, which promoted the phosphorylation of nonmuscle myosin II (NM II) light chain through the activation of ROCK and RhoA activity [18] . In addition, the expression of LPA1, LPA2, and LPA3 in mammary epithelium of transgenic mice induced a high frequency of late-onset, estrogen receptor (ER)-positive, invasive and metastatic mammary cancer [19] . LPA stimulated also tumorigenesis and metastasis in ovarian malignancy [20] .…”
Section: Gpcrs Activated By Bio-active Lipidsmentioning
confidence: 99%
“…LPA levels as high as 10 μmol/L have been reported in ascites fluid of advanced ovarian cancer patients [5] . Mice that overexpress ATX in mammary epithelium develop spontaneous metastatic mammary tumors [72] . Further, the ATX gene is among the top 40 most upregulated genes in metastatic cancers [73] .…”
Section: Overview Of the Atx-lpa-lpp Axis Atx -The Predominant Producmentioning
confidence: 99%
“…Like for ATX, mice that overexpress LPA 1 , LPA 2 or LPA 3 in mammary epithelium develop spontaneous metastatic mammary tumors [72] . LPA 1 and/or LPA 2 receptors are overexpressed in many cancers, particularly gastric, ovarian, breast, colorectal and thyroid cancers compared to healthy tissues [99][100][101][102][103][104] .…”
Section: Lpa Receptor Diversity and Signalingmentioning
confidence: 99%